The HHV-6A Proteins U20 and U21 Target NKG2D Ligands to Escape Immune Recognition - Chaouat, Abigael Eva; Seliger, Barbara; Mandelboim, Ofer; Schmiedel, Dominik (Frontiers in Immunology, 2021)
The coevolution of the human immune system and herpesviruses led to the emergence and diversification of both cellular danger molecules recognized by immune cells on the one hand and viral countermeasures that prevent the expression of these proteins on infected cells on the other. There are eight ligands for the activating receptor NKG2D in humans – MICA, MICB, ULBP1-6. Several of them are induced and surface-expressed on herpesvirus-infected cells to serve as danger signals to activate the immune system. Therefore, these ligands are frequently targeted for suppression by viral immune evasion mechanisms. Mechanisms to downregulate NKG2D ligands and thereby escape immune recognition have been identified in all other human herpesviruses (HHV), except for HHV-6A. In this study, we identify two HHV-6A encoded immunoevasins, U20 and U21, which suppress the expression of the NKG2D ligands ULBP1 and ULBP3, respectively, during infection. Additionally, MICB is targeted by a so far unexplored viral protein. Due to the diminished NKG2D ligand surface expression on infected cells, recognition of HHV-6A infected cells by innate immune cells is impaired. Importantly, our study indicates that immune escape mechanisms between the related herpesviruses HHV-6A and HHV-6B are evolutionary conserved as the same NKG2D ligands are targeted. Our data contribute an additional piece of evidence for the importance of the NKG2D receptor – NKG2D ligand axis during human herpesvirus infections and sheds light on immune evasion mechanisms of HHV-6A.